KEMAMPUAN KOMUNIKASI TERTULIS PESERTA DIDIK PADA MATERI LINGKARAN - dkk, Kristina Kula (Jurnal Pendidikan Matematika, 2019)
COMMUNICATION SKILLS WRITTEN PARTICIPANTS EDUCATE ON CIRCLE MATERIAL. This study aims to describe the ability of written mathematical communication in solving story problems on circle material. The approach used in this study is a qualitative approach to the type of descriptive research. The study was conducted in class VIIA SMP PGRI 6 Malang, with a total of 28 students. Data collection techniques used were tests and interviews. Data analysis was performed based on test results and interviews referring to the criteria of mathematical communication skills using 6 levels of written communication skills in solving story problems. The results showed that the level of written communication skills of students in class VIII A on the material circle was in the low category, this is evident from the percentage of each level that is there for level 0 and for level 1. In the medium category there is for level 2 and for level 3. In the high category there are for level 4 and for level 5. Then the three biggest percentages of each category are taken, among others for the low category at level 0, the medium category at level 2 and the high category at level 4.